Bridging Ayurveda and biochemistry: a scoping review of Agni and metabolism - Gaikwad, Kirti B.; Bhojani, Meera K. (International Journal Of Community Medicine And Public Health, 2026)
Agni is described in Ayurveda as the fundamental principle governing digestion, metabolism, tissue transformation, and vitality. Thirteen types of Agni: Jatharagni, seven Dhatvagni, and five Bhutagni are considered essential for physiological balance. However, their mechanisms remain largely conceptual, with limited systematic correlation to contemporary metabolic science, restricting broader scientific interpretation. A scoping review was conducted following Arksey and O’Malley framework and PRISMA-ScR guidelines. A structured search was performed across PubMed, Web of Science, Google Scholar, DHARA, Ayush Research Portal, and ARD. Studies published between January 2010 and December 2024 were screened. Twenty-four eligible research studies were included for final analysis. Data extraction was performed using JBI SUMARI tool. The included studies demonstrated functional parallels between Jatharagni and digestive enzyme activity, gastric secretions, and enteric regulation. Dhatvagni showed correlation with tissue-level metabolic processes, endocrine modulation, and cellular respiration parameters including thyroid function, lipid profile, glucose metabolism, and mitochondrial activity. Bhutagni was interpreted in relation to hepatic biotransformation, cytochrome P450 pathways, detoxification processes, and immune-metabolic responses. However, objective quantification tools for Agni assessment remain insufficient. The review identifies emerging integrative interpretations between Ayurvedic Agni and modern metabolic science. While conceptual correlations are evident, further structured clinical and molecular research is required for measurable validation.